Scanning electron microscope analysis of 12th-16th century stoneware and porcelain in the archaeology of Singapore and Kota Cina in Sumatra, and its implications - Chi, Alasdair Xin Ren (Nanyang Technological University, 2023)
Stoneware and porcelain artefacts excavated from Kota Cina in Northern Sumatra and Singapore at the end of the Malay Peninsula remain some of the most compelling archaeological evidence of these settlements during the Song to Yuan, and Yuan to Ming dynasties, respectively. In this dissertation, I used scanning electron microscopy to measure these two settlements’ archaeological high-fired ceramics with the aim of inferring formulas for their body pastes and glazes, and employed statistical testing to quantify differences in these formulas within and between ceramic categories recorded at these sites. This was with the goal of determining if ceramic forms and styles corresponded with variations of raw materials and technologies used in making these traded vessels.